Modul Kimia Berbasis EPUB untuk Siswa Tunanetra: Materi Larutan Elektrolit dan Non-Elektrolit - Satrio, Benny Yanuar Dwi (INKLUSI, 2016)
Nowadays, teaching tools, especially for chemistry subject, are limited. Several studies have been conducted to advance the teaching tools through Research and Development approach. The aim of this research is to generate a digital module in chemistry using the subject of electrolyte and non-electrolyte solution through .epub format. This research has been drawn upon procedural development model by Borg and Gall.  The development of Epub module of chemistry has been supervised and peer reviewed by senior lecturers (expert in material and media subject) and senior high school teachers of student with special needs by considering the perspective of student with visual disabilities. The chemistry module has been assessed and scored by material experts with percentage of 87.14% which represents very good quality, whereas the media experts score 85,45% which means a very good quality. According to high school teachers for student with visual disabilities’, the score is 86.4%. The score from 7 students with visual disabilities shows 94% which signifies a very good quality of chemistry module.[Saat ini, media pembelajaran khususnya untuk mata pelajaran kimia masih terbatas. Berbagai studi telah dilakukan untuk mengembangkan media pembelajaran melalui metode Research and Development (R&D). Tujuan penelitian untuk menghasilkan modul digital kimia dengan materi pokok larutan elektrolit dan non elektrolit dalam format .epub. Penelitian telah dilakukan dengan model pengembangan prosedural oleh Borg dan Gall. Pengembangan epub modul kimia dibimbing oleh dosen pembimbing dan mendapatkan penilaian dari peer reviewers, dosen ahli (ahli materi dan ahli media), guru siswa difabel netra, dan siswa difabel netra. Hasil penelitian menunjukkan bahwa modul kimia yang dikembangkan, menurut penilaian ahli materi mendapatkan persentase keidealan 87,14% dan kualitas Sangat Baik (SB), sedangkan menurut penilaian ahli media mendapatkan skor persentase keidealan 85,45% dan kualitas Sangat Baik (SB). Berdasarkan penilaian guru siswa difabel netra SMA/MA, modul kimia mendapatkan persentase keidealan 86,40% dan kualitas Sangat Baik (SB) dan berdasarkan respons tujuh siswa difabel netra mendapatkan persentase keidealan 94%.]